AN INTERVENTION PROGRAM FOR THE DEVELOPMENT OF LEARNING TO LEARN COMPETENCY OF 11TH GRADE STUDENTS WITH LEARNING DIFFICULTIES IN STUDYING ROMANIAN LANGUAGE AND LITERATURE - LORENA PECULEA; MUȘATA BOCOȘ (Studia Universitatis Babes-Bolyai, 2015)
ABSTRACT. Education and training have to provide the learning environment for the development of learning to learn competency for all citizens, including those with fewer opportunities. The main purpose of the formative experiment proposed in this paper was to develop and implement a formative intervention program focused on developing an operational model of learning to learn competency on cognitive, metacognitive and non-cognitive dimensions for 11th grade students with learning difficulties at Romanian Language and Literature. The sample of subjects consisted in 106 students of 11th grade with learning difficulties from three technical high schools and colleges. Using critical reflection, metacognitive reflection, strategic decision making and training subjects in complex, analytical and creative learning situations with interdisciplinary links in an articulated intervention program proved to be efficient in activating and optimizing learning behavior and therefore, in decreasing the frequency learning difficulties. The statistically significant differences between pretest and posttest results in conjunction with developments, highlighted by quantitative and qualitative benchmarks, of subjects in the experimental group during the formative intervention allow us to appreciate that the assumption underlying the experimental study was validated.